All the functions proposed have the same pattern :

f(x)=a(x+3)^2(x+1)(x-2)^2(x-3) which corresponds to the graph regarding the function's zero. We have to determine a

let's calculate f(0)

f(0)=a*3^2*1*2^2*(-3)=-108a

in the graph we see that f(0)=-12 so

-108a = -12 and a = 12/108=1/9

The correct answer is A.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up